2019
DOI: 10.5194/acp-2019-974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of Age of Air Trends on the derivation method for non-linear increasing tracers

Abstract: <p><strong>Abstract.</strong> Mean age of air (AoA) is a diagnostic of transport along the stratospheric Brewer-Dobson circulation. While models consistently show negative trends, long-term time series (1975–2016) of AoA derived from observations show non-significant positive trends in mean AoA in the northern hemisphere. This discrepancy between observed and modeled mean AoA trends is still not resolved. There are uncertainties and assumptions required w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In its presented form, all derived inverse age spectra assume the tropical tropopause to be a single source region into the stratosphere. Although this appears valid for the upper and middle stratosphere (Fueglistaler et al, 2009), studies have shown that for the lowermost extratropical stratosphere, quasi-isentropic transport across the local tropopause has critical influence and strongly affects trace gas burdens in that region (Hoor et al, 2005;Bönisch et al, 2009). Therefore, the assumption of single entry through the tropical tropopause layer is insufficient to estimate a precise age spectrum and must be modified to include air entrainment through the complete tropopause together with related seasonality.…”
Section: Inverse Methods -General Approach and Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In its presented form, all derived inverse age spectra assume the tropical tropopause to be a single source region into the stratosphere. Although this appears valid for the upper and middle stratosphere (Fueglistaler et al, 2009), studies have shown that for the lowermost extratropical stratosphere, quasi-isentropic transport across the local tropopause has critical influence and strongly affects trace gas burdens in that region (Hoor et al, 2005;Bönisch et al, 2009). Therefore, the assumption of single entry through the tropical tropopause layer is insufficient to estimate a precise age spectrum and must be modified to include air entrainment through the complete tropopause together with related seasonality.…”
Section: Inverse Methods -General Approach and Problemsmentioning
confidence: 99%
“…Mechanical drivers of the BDC are planetary-and synoptic-scale atmospheric waves that get excited in the troposphere and propagate upward into the extratropical middle stratosphere where they finally break and transfer their momentum to induce a poleward motion (Haynes et al, 1991;Holton et al, 1995). The wave drag causes air to rise slowly in the tropics mainly through the tropical tropopause layer (TTL) to compensate for the poleward drift (Fueglistaler et al, 2009). Eventually, air descends at higher latitudes back into the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation uses a polynomial fit to the reference time series to approximate mean AoA. However, in our study we modified the parameters compared to those used in Engel et al (2009) to ensure that (passive) SF 6 -based AoA agrees with the ideal AoA derived from the linear tracer, following Fritsch et al (2019). Specifically, in our calculations we used a ratio of moments of 1.0 years and a fraction of input of 95 %.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The timeseries of the realistic SF 6 tracer emissions show a stronger increase in the 1980s (not shown). Fritsch et al (2019) showed that due to this increase the calculation of AoA based on SF 6 -like tracers is more sensitive to the chosen parameters in the AoA derivation for this time. The drop in AoA we see is caused by this limitation of the derivation from SF 6 -like tracers.…”
Section: Explanations For Apparent Age Of Air Trendsmentioning
confidence: 99%
“…The model used in this work is EMAC, the MESSy (Modular Earth Submodel System) version of the ECHAM5 climate model (see Jöckel et al (2010) for details on EMAC and Roeckner et al (2006) for details on ECHAM5). EMAC is a modern chemistry-climate model which is commonly used for studies of the stratosphere and upper troposphere (Sinnhuber and Meul, 2015;Oberländer-Hayn et al, 2016;Fritsch et al, 2019), as well as studies of the troposphere. In this work, EMAC is operated at the T42L90MA spectral resolution, corresponding to a horizontal quadratic Gaussian grid of approximately 2.8 •…”
Section: Modelsmentioning
confidence: 99%